Trends in the Incidence of Hypertensive Disorders of Pregnancy Among the Medicaid Population before and During COVID-19 - Jessica Lin; Heidi Feng; Ronald Horswell; San Chu; Yun Shen; Gang Hu (Women's Health Reports)
Importance: Hypertensive disorders of pregnancy (HDP) are a group of high blood pressure disorders during pregnancy that are a leading cause of maternal and infant morbidity and mortality. Data on the trend in the incidence of HDP among the Medicaid population during coronavirus disease of 2019 (COVID-19) are lacking. Objective: To determine the trends in the annual incidence of HDP among pregnant Medicaid-insured women in Louisiana before and during the COVID-19 pandemic (2016–2021). Methods: A total of 113,776 pregnant women aged 15–50 years were included in this study. For multiparous individuals, only the first pregnancy was used in the analyses. Women with a diagnosis of each type-specific HDP were identified by using the International Classification of Diseases, 10th revision (ICD-10) codes. The annual incidence of HDP was calculated for each race and age subgroup. For each type-specific HDP, the annual age-specific incidence was calculated. Results: The incidence of HDP increased from 10.5% in 2016 to 17.7% in 2021. The highest race/ethnicity-specific incidence of HDP was seen in African American women (19.2%), then White women (13.1%), followed by other women (10.7%). Conclusion and Relevance: HDP remains a very prevalent and significant global health issue, especially in African American women and during the COVID-19 pandemic. Severe HDP substantially increases the risk of mortality in offspring and poses long-term issues for both mother and infant. HDP prevention holds particular relevance for the Medicaid population, given the health care disparities and barriers that impact quality of care, leading to an increased risk for HDP.